An assessment of the level of knowledge of health professionals on nutrition and diabetes self-management in treating patients with type 1 and type 2 diabetes Mellitus in South Africa - Catsicas, Maria Elizabeth (Stellenbosch : Stellenbosch University, 2014)
Thesis (MNutr)--Stellenbosch University, 2014.